2015
DOI: 10.1021/acs.jpcc.5b04145
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Activation of CO on Co3O4(111) Thin Films

Abstract: To explore the catalytic properties of cobalt oxide at the atomic level, we have studied the interaction of CO and O 2 with well-ordered Co 3 O 4 (111) thin films using scanning tunneling microscopy (STM), high-resolution X-ray photoelectron spectroscopy (HR-XPS), infrared reflection absorption spectroscopy (IRAS), and temperature-programmed desorption spectroscopy (TPD) under ultrahigh vacuum (UHV) conditions. At low coverage and temperature CO binds to surface Co 2+ ions on the (111) facets. At larger exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 63 publications
9
91
0
Order By: Relevance
“…49). In agreement with the STM results discussed in Section 3.1, this observation clearly shows that the deposited Co does not form three-dimensional metallic islands, as is normally observed for metal deposition on oxide surfaces.…”
Section: Co Adsorption At Co Deposits In Co 3 O 4 (111)/ir(100) Probesupporting
confidence: 90%
See 2 more Smart Citations
“…49). In agreement with the STM results discussed in Section 3.1, this observation clearly shows that the deposited Co does not form three-dimensional metallic islands, as is normally observed for metal deposition on oxide surfaces.…”
Section: Co Adsorption At Co Deposits In Co 3 O 4 (111)/ir(100) Probesupporting
confidence: 90%
“…49 We found that at low exposure CO adsorbs at Co 2+ centers, giving rise to a sharp band around 2170 cm À1 . 49 We found that at low exposure CO adsorbs at Co 2+ centers, giving rise to a sharp band around 2170 cm À1 .…”
Section: Co Adsorption At Co Deposits In Co 3 O 4 (111)/ir(100) Probementioning
confidence: 63%
See 1 more Smart Citation
“…S5 of the supplementary material), which corresponds to saturation of the defect peaks plus 1% of the monolayer coverage, reveal a single peak at 291.3 eV, identical to that of the physisorbed monolayer. Since carbonate species typically appear in the range 287-289 eV, 39,40 we conclude that CO 2 adsorbed at defects is also physisorbed.…”
Section: B Photoelectron Spectroscopymentioning
confidence: 79%
“…8(a)], due to conversion to a spinel Co 3 O 4 (100) film. In the corresponding C 1s spectrum recorded at 300 K we observe two peaks located at 288.7 eV and 291.2 eV assigned to carbonates (Ferstl et al, 2015) and gas-phase CO molecules, respectively. The intensity of the carbonate component first increases upon heating and reaches a maximum at a temperature of 350 K. At higher temperature the intensity of the carbonate component decreases and at 500 K no carbonates are left on the surface.…”
Section: Apxps Study Of Co Oxidation On Ag(100)-supported Co Oxide Filmsmentioning
confidence: 90%